2020
DOI: 10.1007/s13595-020-00954-0
|View full text |Cite
|
Sign up to set email alerts
|

Using forest gap models and experimental data to explore long-term effects of tree diversity on the productivity of mixed planted forests

Abstract: Key message In this exploratory study, we show how combining the strength of tree diversity experiment with the long-term perspective offered by forest gap models allows testing the mixture yielding behavior across a full rotation period. Our results on a SW France example illustrate how mixing maritime pine with birch may produce an overyielding (i.e., a positive net biodiversity effect). Context Understanding the link between tree diversity and stand productivity is a key issue at a time when new forest m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 90 publications
(127 reference statements)
3
15
0
Order By: Relevance
“…The latter is confirmed as fine root biomass per species was proportional to its basal area (Table 2). It is logical to expect that since pine grew faster than birch (Morin et al 2020), it would also take up water faster, and would outcompete the relatively slower growing birch trees, leaving less available water in the soil. In addition, birch has finer roots than pine, and it might be more sensitive to unfavourable moisture conditions, which might occur more frequently in the very permeable sandy soils that "hold" less water.…”
Section: Depth-specific Effects On Relative Yieldmentioning
confidence: 99%
“…The latter is confirmed as fine root biomass per species was proportional to its basal area (Table 2). It is logical to expect that since pine grew faster than birch (Morin et al 2020), it would also take up water faster, and would outcompete the relatively slower growing birch trees, leaving less available water in the soil. In addition, birch has finer roots than pine, and it might be more sensitive to unfavourable moisture conditions, which might occur more frequently in the very permeable sandy soils that "hold" less water.…”
Section: Depth-specific Effects On Relative Yieldmentioning
confidence: 99%
“…By virtually manipulating the composition of simulated forest communities, forest IBMs have proven useful in exploring the effect of species richness and functional composition on ecosystem properties (e.g., Fischer et al, 2018). Simulations reproduced positive relationships between (species or functional) diversity and productivity or biomass, in agreement with observed patterns (Maréchaux & Chave, 2017;Morin et al,2011Morin et al, , 2020, further motivating a finer-grained representation of diversity in DGVMs. These studies demonstrated how competition for light can induce this positive effect in heterogeneous forests.…”
Section: Biodiversity and Ecosystem Functioningmentioning
confidence: 57%
“…The copyright holder for this preprint this version posted May 9, 2021. ; https://doi.org/10.1101/2021.05.07.443133 doi: bioRxiv preprint time (Morin et al, 2020). Oaks species with their slower growth rates and varying drought and shade tolerances will gradually establish into stands, leading to a stand stratification possibly suitable to mixed stands, even though at this point, there is no consensus on the stage of forest development for which the positive effect of diversity peak (Jucker et al, 2020;Taylor et al, 2020).…”
Section: § Species Substitution Trigged Overyielding In Mixture Of Two Pioneer Speciesmentioning
confidence: 99%